Balancing agency and automation to overcome digital divide in ESP writing instruction - Arshad, Sadia; Irshad, Sadia; Batool, Huma (Journal of International Students, 2026)
In the digital age, technology access and application inequalities, conceptualized as the digital divide, present a continuing problem for English for Specific Purposes writing education. This qualitative research explores the experience of the digital divide among ESP teachers in terms of four levels of access to van Dijk and how they view technological determinism as a factor in defining pedagogical engagement with digital tools. The data were gathered through open-ended questionnaires and analyzed using thematic analysis. The results demonstrate an unequal distribution of technology integration, influenced by infrastructural constraints, institutional support, disparate levels of digital literacy, and ethical issues related to the use of automated writing tools. While some teachers resisted due to motivational and material constraints, others adopted innovative practices, reflecting a soft determinist view. The paper highlights the importance of continuous professional growth, institutional support, and explicit policy guidelines to achieve equitable digital integration in ESP writing pedagogy.